'Not an Idle Spectator': Geoffrey Hill as Model Reviewer. (February 2013) - Vincent, Bridget
Geoffrey Hill's prose has prompted longstanding critical controversy, much of which turns on the perceived difficulty, intransigence and anachronism of his oeuvre as a whole. This paper proposes that new ways to navigate this controversy can be found in Hill's preoccupation with the exemplary dimensions of writing – that is, in his interest in the poet's capacity to offer examples (positive and negative) to a community of readers. The discussion pays particular attention to the connections Hill's reviews establish between style and ethical choice and between literary difficulty and democracy; connections which are intertwined with his ethics of exemplarity in fundamental ways. The paper also engages with those dimensions of literary exemple-use which emerge in new or unusual ways in his prose: his presentation of 'models' or ideals for the organisation of civil society; his treatment of certain literary works as exemplars or embodiments of philosophical ideas; and his procedural tic of 'sampling' regularly for the purpose of chastisement the 'bad example' set by some of the works he criticises.